Hubungan Kepercayaan Diri Terhadap Kecemasan Sosial pada Siswa Kelas VII A dan VII B SMP Negeri 20 Surakarta Tahun Ajaran 2024 / 2025 - Viony Rahmawati (Universitas Maritim AMNI Semarang, 2025)
Adolescence is a challenging developmental phase, where social anxiety can affect students' social well-being. Self-confidence is believed to be a key factor in reducing social anxiety. This study aims to explore the relationship between self-confidence and social anxiety.This research employs a quantitative method using self-confidence and social anxiety scales as instruments. Data analysis was conducted using Pearson correlation techniques in SPSS version 23. The results indicate a significant negative correlation between self-confidence and social anxiety among middle school students. The higher a student's self-confidence, the lower their social anxiety, and vice versa.It is expected that this study can serve as a foundation for developing intervention programs aimed at enhancing students' self-confidence, enabling them to interact more effectively and achieve academic success.